2006
DOI: 10.21836/pem20060209
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound-guided reduction of twin pregnancies in the mare

Abstract: ZusammenfassungZwillingsgraviditäten bei der Stute bewirken ökonomische Verluste, da sie im Regelfall zu Aborten, Totgeburten bzw. zur Entwicklung lebensschwacher oder deformierter Fohlen führen. Die transvaginale ultraschallgeleitete Aspiration ist eine effiziente Methode um eine Reduktion zu erreichen. In der vorliegenden Studie wurde bei 27 Zwillingsträchtigkeiten einmalig zwischen dem 21. bis 52. Trächtigkeitstag Fruchtwasser von einem Konzeptus aspiriert. Insgesamt wurde nach 10 bis 14 Tagen eine Überlebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The proportion of similar versus dissimilar vesicle size in twin pregnancies had no significant effect on foaling rate after TUA was performed in our study. Although the earlier the TUA is performed the better the success rate, we recommend to delay TUA in cases in which there is a strong discrepancy in conceptus size (>50%) for 3-5 days to allow These results are in accordance with Becker et al, 16 who did not observe increased pregnancy rates after administering flunixin meglumine for 5-6 days after TUA was performed.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The proportion of similar versus dissimilar vesicle size in twin pregnancies had no significant effect on foaling rate after TUA was performed in our study. Although the earlier the TUA is performed the better the success rate, we recommend to delay TUA in cases in which there is a strong discrepancy in conceptus size (>50%) for 3-5 days to allow These results are in accordance with Becker et al, 16 who did not observe increased pregnancy rates after administering flunixin meglumine for 5-6 days after TUA was performed.…”
Section: Discussionsupporting
confidence: 86%
“…reports on the effect of gestational age of the twin embryos/fetuses on the pregnancy and foaling rates after TUA. Some studies have reported a decrease in pregnancy rate when TUA was performed after D 36 16,19 or D 42 20 but others found no negative impact of increasing gestational age on pregnancy rate after TUA. 18,21 In the present study, overall higher pregnancy and foaling rates were achieved when TUA was performed earlier in gestation (D 25-29, 64.7%; D 30-34, 47.4%; D 35-39, 39.7%), and a significantly lower fetal survival was observed when TUA was performed after D 40.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations